Pseudouridines in U2 snRNA stimulate the ATPase activity of Prp5 during spliceosome assembly. (12th February 2016) - Wu, Guowei; Adachi, Hironori; Ge, Junhui; Stephenson, David; Query, Charles C; Yu, Yi‐Tao
Abstract: Pseudouridine (Ψ) is the most abundant internal modification identified in RNA, and yet little is understood of its effects on downstream reactions. Yeast U2 snRNA contains three conserved Ψs (Ψ35, Ψ42, and Ψ44) in the branch site recognition region (BSRR), which base pairs with the pre‐mRNA branch site during splicing. Here, we show that blocks to pseudouridylation at these positions reduce the efficiency of pre‐mRNA splicing, leading to growth‐deficient phenotypes. Restoration of pseudouridylation at these positions using designer snoRNAs results in near complete rescue of splicing and cell growth. These Ψs interact genetically with Prp5, an RNA‐dependent ATPase involved in monitoring the U2 BSRR‐branch site base‐pairing interaction. Biochemical analysis indicates that Prp5 has reduced affinity for U2 snRNA that lacks Ψ42 and Ψ44 and that Prp5 ATPase activity is reduced when stimulated by U2 lacking Ψ42 or Ψ44 relative to wild type, resulting in inefficient spliceosome assembly. Furthermore, in vivo DMS probing analysis reveals that pseudouridylated U2, compared to U2 lacking Ψ42 and Ψ44, adopts a slightly different structure in the branch site recognition region. Taken together, our results indicate that the Ψs in U2 snRNA contribute to pre‐mRNA splicing by directly altering the binding/ATPase activity of Prp5. Synopsis: Activation of the DEAD‐box helicase Prp5 requires pseudouridine formation, shedding light on the regulatory potential of such increasingly recognized RNA modifications. Pseudouridines (Ψ35, Ψ42, and Ψ44) in the U2 branch site recognition region are important for spliceosome assembly, pre‐mRNA splicing, and cell growth. Ψ42 and Ψ44 interact genetically with Prp5 and promote direct interaction of U2 with Prp5. U2 pseudouridylation also stimulates Prp5's RNA‐dependent ATPase activity. Pseudouridylation alters the U2 local structure, thereby contributing to Prp5 binding. Abstract : Activation of the DEAD‐box helicase Prp5 requires pseudouridine formation, shedding light on the regulatory potential of such increasingly recognized RNA modifications.